EFFECT OF TRAINING, USE OF SIPKD, COMPETENCE AND INTERNAL CONTROL ON QUALITY OF FINANCIAL STATEMENTS IN SKPD BIREUEN REGENCY WITH STYLE LEADERSHIP AS VARIABLES MODERATING - yuswardi, yuswardi (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of training, the use ofinformation system, regional financial management, competence, and internal control onfinancial statement quality with leadership style as moderating variable. The research usedassociative causal method, using primary data and questionnaires. The population was 94financial managers and treasuers. The data were analyzed by using multiple linear regressionanalysis and moderating variable with residual test. The result of the research showed that,simultaneouly training, the use of information system, regional financial management,competence, and internal control had siginifant influence on financial statement quality.Partially, training, the use of information system, regional financial management,competence, and internal control had siginifant influence on financial statement quality.Leadership style could not moderate the correlation of training, the use of informationsystem, regional financial management, competence, and internal control with financialstatement quality.